A lithium-carbon fluoride battery positive plate, its preparation method and application

CN120247009BActive Publication Date: 2026-10-16NANTONG REN INNOVATION ENERGY TECHNOLOGY CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510280617.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2026-10-16
Estimated Expiration
2045-03-11

AI Technical Summary

Technical Problem

该方法中由于反应过程为气固反应,且为放热反应,一旦反应过剧烈,就会造成瞬间压力及温度升高,出现炸膛事故,安全隐患大

Benefits of technology

1、本发明的一种锂氟化碳电池正极片及其制备方法和应用,利用本身气源流动的方法,通过精确控制气体流量,带走部分反应热,使得氟化反应安全稳定的进行,从而解决氟化过程中由于反应过热而造成的炸膛安全隐患。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120247009B_ABST
    Figure CN120247009B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of batteries, in particular to a lithium carbon fluoride battery positive plate and a preparation method and application thereof. Graphite is placed in a fluorination reactor, fluorination gas is filled into the fluorination reactor, fluorination reaction is carried out, and fluorinated graphite is obtained; when the pressure in the fluorination reactor exceeds 200 kPa, a pressure relief valve is opened, the fluorination gas enters a cooler to be cooled, and then enters a gas circulating pump to be circulated and returned to the fluorination reactor. The application utilizes the gas flow method, accurately controls the gas flow, and carries away part of the reaction heat, so that the fluorination reaction is safely and stably carried out, thereby solving the safety hidden danger of burst caused by overheating in the fluorination process. The fluorinated graphite, a conductive agent, a binder and a solvent are uniformly mixed to obtain positive paste; the positive paste is coated on a current collector, dried, and then rolled to obtain the lithium carbon fluoride battery positive plate, which has excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, specifically to a lithium fluoride carbon battery positive electrode sheet, its preparation method, and its application. Background Technology

[0002] Lithium fluoride carbon batteries (Li / CFx) are primary batteries that use fluoride carbon as the positive electrode and metallic lithium as the negative electrode. They are currently the next generation of lightweight batteries with the highest specific energy among primary batteries. Furthermore, due to their extremely low self-discharge, excellent storage performance, wide operating temperature range, and environmental friendliness, these batteries are widely used in cutting-edge technology fields such as national defense, aerospace, and medical implants.

[0003] The key electrode material in lithium-ion fluorinated carbon batteries is fluorinated carbon. The main methods for preparing fluorinated carbon include high-temperature gas-phase fluorination, low-temperature fluorination, plasma methods, and electrolytic synthesis. Currently, the industrially viable method is high-temperature gas-phase fluorination, which commonly uses graphite as the carbon material to produce fluorinated graphite. The reactors used in this method are mostly static reactors, lacking precise control of gas flow. Because the reaction process is a gas-solid reaction and exothermic, excessively vigorous reaction can cause a sudden increase in pressure and temperature, leading to a potential explosion and posing a significant safety hazard.

[0004] Furthermore, due to the poor conductivity, low surface energy, and poor permeability of fluorinated carbon materials, polarization is easily caused when fluorinated carbon materials are used as electrode materials for lithium primary batteries, resulting in poor rate performance of lithium fluorinated carbon batteries and failure to meet the requirements of high-power discharge.

[0005] Therefore, we propose a lithium fluoride carbon battery cathode sheet, its preparation method, and its application. Summary of the Invention

[0006] The purpose of this invention is to provide a lithium fluoride carbon battery positive electrode sheet, its preparation method, and its application, so as to solve the problems raised in the prior art.

[0007] To achieve the above-mentioned objectives, the present invention provides the following technical solution: A method for preparing fluorinated graphite includes the following steps: Graphite is placed in fluorination reactor 2, and fluorinated gas source 1 is introduced. The pressure in fluorination reactor 2 is controlled at 100-150 kPa to carry out the fluorination reaction and obtain fluorinated graphite. When the pressure in fluorination reactor 2 exceeds 200 kPa, the pressure relief valve 3 is opened, and the fluorinated gas source enters the cooler 4 for cooling, and then enters the gas circulation pump 5 to circulate back to fluorination reactor 2.

[0008] Furthermore, the fluorinated gas source 1 is one or more of F2, ClF, ClF3, and NF3.

[0009] Furthermore, the reaction conditions in the fluorination reactor 2 are: reaction temperature 300-500℃, reaction time 5-30h.

[0010] Furthermore, the gas circulation pump 5 controls the gas flow rate to be 0.5-1.0 m³ / h. 3 / h.

[0011] Furthermore, the fluorinated graphite has a fluorine-to-carbon ratio of 0.5-0.9.

[0012] In the above technical solution, the gas circulation pump has a sealed structure, allowing only inflow and not outflow when closed, and it is equipped with flow control, enabling precise control of the gas flow rate, which is maintained between 0.5-1.0 m³ / h. 3 A flow rate that is too low will not carry away the heat of reaction, while a flow rate that is too high will easily carry away excessive heat, resulting in an incomplete fluorination reaction.

[0013] A method for preparing a positive electrode sheet for a lithium fluoride carbon battery, characterized by comprising the following steps: Step S1: Mix the fluorinated graphite, conductive agent, binder and solvent as described in claim 5 evenly to obtain the positive electrode slurry; Step S2: Coat the positive electrode slurry onto the current collector, dry it, and then roll it to obtain the positive electrode sheet of the lithium fluoride carbon battery.

[0014] Furthermore, the mass ratio of the fluorinated graphite, conductive agent, and binder is (80-95):(2-10):(3-10).

[0015] Furthermore, the fluorinated graphite undergoes modification treatment, the specific process of which is as follows: Step (1): Fluorinated graphite is subjected to mixed plasma treatment to obtain pretreated fluorinated graphite; Step (2): Heat the polyvinyl alcohol solution to 70-80℃, add sodium hydroxide solution to adjust the pH to 9-10, add 2,3-epoxypropyltrimethylammonium chloride, react for 4-6 hours, cool to room temperature, adjust the pH to neutral, and obtain the modified polyvinyl alcohol solution. Step (3): Mix the modified polyvinyl alcohol solution and 6-aminoquinoline evenly, introduce nitrogen gas, add isocyanate methacrylate and dibutyltin dilaurate, react at 65-75℃ for 6-8h, cool to room temperature, add deionized water to obtain solution A; Step (4): Mix solution A and pretreated fluorinated graphite evenly, introduce nitrogen gas, add 3,4-ethylenedioxythiophene, adjust the pH of the system to 2-3 with hydrochloric acid, add ammonium persulfate dropwise over 30-50 minutes, react under ice-water bath conditions for 22-24 hours, and obtain modified fluorinated graphite after centrifugation, washing and drying.

[0016] Furthermore, in step (1), the plasma treatment process conditions are as follows: the working atmosphere is C2H2 / Ar, C2H2:Ar=1:(1-2), the treatment time is 10-20min, the treatment power is 200-250W, the vacuum degree is 15-40Pa, and the treatment temperature is 25-300℃.

[0017] Furthermore, in step (2), the mass of 3-epoxypropyltrimethylammonium chloride is 10-20% of the mass of the polyvinyl alcohol solution.

[0018] Furthermore, in step (3), the mass ratio of the modified polyvinyl alcohol solution to 6-aminoquinoline is 1:(0.1-0.2).

[0019] Furthermore, in step (3), the mass of isocyanate methacrylate is 2-3 times the mass of 6-aminoquinoline.

[0020] Furthermore, in step (3), the mass ratio of isocyanate methacrylate to dibutyltin dilaurate is 1:(0.01-0.03).

[0021] Furthermore, in step (3), the solid content of solution A is 20%.

[0022] Furthermore, in step (4), the mass ratio of solution A to pretreated fluorinated graphite is 1:(0.05-0.10).

[0023] Furthermore, in step (4), the mass of 3,4-ethylenedioxythiophene is 1-2 times the mass of fluorinated graphite.

[0024] Furthermore, in step (4), the mass of ammonium persulfate is 3-5% of the mass of 3,4-ethylenedioxythiophene.

[0025] In the above technical solution, C2H2 / Ar mixed plasma is used to modify fluorinated graphite, which reduces the surface high-fluorine layer of the fluorinated carbon material, increases the surface carbon content, increases the number of highly electrochemically active half-ionic carbon-fluorine bonds, and reduces the carbon-fluorine bond energy, thereby improving the rate performance of the battery. Polyvinyl alcohol (PVA) is a hydrophilic substance with a large number of hydrogen bonds in its molecular chain. It has good water solubility, mechanical properties, film-forming properties, and biodegradability. 3-epoxypropyltrimethylammonium chloride is used to modify polyvinyl alcohol, introducing quaternary ammonium salt groups on the PVA side chain. Then, 6-aminoquinoline and the modified polyvinyl alcohol solution are mixed evenly. Subsequently, under the action of dibutyltin dilaurate catalyst, it continues to react with isocyanate methacrylate to introduce quinoline groups and double bonds. It can react with 3,4-ethylenedioxythiophene conductive polymer monomers to introduce thiophene groups. Through polymerization reaction, a coating layer with a network structure is formed on the surface of fluorinated graphite, which can further improve the structural stability of the cathode material.

[0026] Furthermore, the conductive agent is at least one of conductive graphite, conductive carbon black, carbon nanotubes, and graphene.

[0027] Furthermore, the adhesive is polyvinylidene fluoride.

[0028] Furthermore, the solid content of the positive electrode slurry is 50-70%.

[0029] Furthermore, the solvent is N-methylpyrrolidone.

[0030] Furthermore, the current collector is aluminum foil.

[0031] Furthermore, the thickness of the positive electrode plate is 100-200 μm.

[0032] Compared with the prior art, the beneficial effects of the present invention are: 1. The present invention relates to a lithium fluorinated carbon battery positive electrode sheet, its preparation method and application, which utilizes the gas source flow method to precisely control the gas flow rate and remove part of the reaction heat, so that the fluorination reaction can proceed safely and stably, thereby solving the safety hazard of chamber explosion caused by overheating during the fluorination process.

[0033] 2. This invention relates to a lithium fluoride carbon battery positive electrode sheet, its preparation method, and its application. Plasma thinning of the high-fluorine layer on the surface of the fluoride carbon material increases the surface carbon content, increases the number of highly electrochemically active half-ionic carbon-fluorine bonds, reduces the carbon-fluorine bond energy, and improves the battery's rate performance. 3-Epoxypropyltrimethylammonium chloride is used to modify polyvinyl alcohol (PVA) by introducing quaternary ammonium salt groups onto the PVA side chain, resulting in a modified PVA solution. Then, 6-aminoquinoline and the modified PVA solution are mixed uniformly, and subsequently, under the action of a dibutyltin dilaurate catalyst, the process continues... Continuing the reaction with isocyanate methacrylate to introduce quinoline groups and double bonds, it can react with 3,4-ethylenedioxythiophene conductive polymer monomers to introduce thiophene groups, thereby forming a network-structured coating layer on the surface of fluorinated graphite, improving coating uniformity and greatly enhancing the structural stability of the cathode material. Among them, quinoline and quaternary ammonium salts have dual electronic and ion conduction capabilities, which can effectively improve the rate and cycle performance of the battery. The presence of thiophene groups can improve the conductivity of the material and promote electron transport in the electrode, thereby further improving the overall performance of the battery. Attached Figure Description

[0034] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used in conjunction with embodiments of the invention to explain the invention and do not constitute a limitation thereof. In the drawings: Figure 1 This is a flowchart illustrating the present invention; In the diagram: 1 is the fluorinated gas source, 2 is the fluorination reactor, 3 is the pressure relief valve, 4 is the cooler, and 5 is the gas circulation pump. Detailed Implementation

[0035] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0036] It should be noted that there are no special restrictions on the suppliers of all raw materials involved in this invention. Exemplary sources include: graphite with a particle size of 5-10 μm, sourced from Luoyang Tongrun Information Technology Co., Ltd.; current collector: aluminum foil, 12 μm thick, grade H18-1100, sourced from Shenzhen Honglei Metal Materials Co., Ltd.; conductive agent: conductive carbon black SUPER P Li (Swiss Temiko), sourced from Guangdong Lvwei New Materials Technology Co., Ltd.; binder: polyvinylidene fluoride, grade KF7200 from Kureha, Japan, sourced from Shanghai Huaheng Hui New Materials Technology Co., Ltd.; polyvinyl alcohol solution: grade Kuraray 205 from Japan, with a solid content of 20%.

[0037] Example 1: A method for preparing fluorinated graphite, comprising the following processes: Graphite was placed in a fluorination reactor, F2 was introduced, and the pressure in fluorination reactor 2 was controlled at 100 kPa to carry out the fluorination reaction (reaction temperature 300℃, reaction time 30 h) to obtain fluorinated graphite. When the pressure in the fluorination reactor exceeded 200 kPa, the pressure relief valve was opened, and the fluorinated gas source entered a cooler for cooling, and then entered a gas circulation pump for recirculation back to the fluorination reactor. The gas circulation pump controlled the gas flow rate at 0.5 m³ / h. 3 / h; A method for preparing a positive electrode sheet for a lithium fluoride carbon battery includes the following processes: Step S1: Mix 160g of fluorinated graphite, 4g of conductive agent, 6g of binder and N-methylpyrrolidone evenly to obtain a positive electrode slurry with a solid content of 50%; Step S2: Coat the positive electrode slurry onto the current collector, dry it, and then roll it to obtain the positive electrode sheet of the lithium fluoride carbon battery.

[0038] Example 2: A method for preparing fluorinated graphite, comprising the following steps: Graphite was placed in a fluorination reactor, F2 was introduced, and the pressure in fluorination reactor 2 was controlled at 120 kPa to carry out the fluorination reaction (reaction temperature 400℃, reaction time 10 h) to obtain fluorinated graphite. When the pressure in the fluorination reactor exceeded 200 kPa, the pressure relief valve was opened, and the fluorinated gas source entered a cooler for cooling, and then entered a gas circulation pump for recirculation back to the fluorination reactor. The gas circulation pump controlled the gas flow rate at 0.6 m³ / h. 3 / h; A method for preparing a positive electrode sheet for a lithium fluoride carbon battery includes the following processes: Step S1: Mix 170g of fluorinated graphite, 10g of conductive agent, 10g of binder and N-methylpyrrolidone evenly to obtain a positive electrode slurry with a solid content of 55%; Step S2: Coat the positive electrode slurry onto the current collector, dry it, and then roll it to obtain the positive electrode sheet of the lithium fluoride carbon battery; Fluorinated graphite undergoes modification treatment, the specific process of which is as follows: Step (1): Fluorinated graphite is subjected to mixed plasma treatment (the process conditions for plasma treatment are: working atmosphere is C2H2 / Ar, C2H2:Ar=1:1, treatment time is 10min, treatment power is 200W, vacuum degree is 15Pa, and treatment temperature is 25℃) to obtain pretreated fluorinated graphite; Step (2): Heat 3400g of polyvinyl alcohol solution to 70℃, add sodium hydroxide solution to adjust pH=9, add 340g of 2,3-epoxypropyltrimethylammonium chloride, react for 4h, cool to room temperature, adjust pH to neutral, and obtain modified polyvinyl alcohol solution; Step (3): Mix 3400g of modified polyvinyl alcohol solution and 340g of 6-aminoquinoline evenly, react for 3h, introduce nitrogen gas, add 680g of isocyanate methacrylate and 6.8g of dibutyltin dilaurate, react at 65℃ for 6h, cool to room temperature, add deionized water to obtain solution A with a solid content of 20%; Step (4): Mix 3400g of solution A and 170g of pretreated fluorinated graphite evenly, add 170g of 3,4-ethylenedioxythiophene, adjust the pH of the system to 2 with 1mol / L hydrochloric acid, add 5.1g of ammonium persulfate dropwise over 30min, react for 22h under ice-water bath conditions, and obtain modified fluorinated graphite after centrifugation, washing and drying.

[0039] Example 3: A method for preparing fluorinated graphite, comprising the following steps: Graphite was placed in a fluorination reactor, F2 was introduced, and the pressure in fluorination reactor 2 was controlled at 130 kPa to carry out the fluorination reaction (reaction temperature 450℃, reaction time 20 h) to obtain fluorinated graphite. When the pressure in the fluorination reactor exceeded 200 kPa, the pressure relief valve was opened, and the fluorinated gas source entered a cooler for cooling, and then entered a gas circulation pump for recirculation back to the fluorination reactor. The gas circulation pump controlled the gas flow rate at 0.8 m³ / s. 3 / h; A method for preparing a positive electrode sheet for a lithium fluoride carbon battery includes the following processes: Step S1: Mix 180g of fluorinated graphite, 14g of conductive agent, 16g of binder and N-methylpyrrolidone evenly to obtain a positive electrode slurry with a solid content of 60%. Step S2: Coat the positive electrode slurry onto the current collector, dry it, and then roll it to obtain the positive electrode sheet of the lithium fluoride carbon battery; Fluorinated graphite undergoes modification treatment, the specific process of which is as follows: Step (1): Fluorinated graphite is subjected to mixed plasma treatment (the process conditions for plasma treatment are: working atmosphere is C2H2 / Ar, C2H2:Ar=1:1.5, treatment time is 15min, treatment power is 220W, vacuum degree is 30Pa, and treatment temperature is 100℃) to obtain pretreated fluorinated graphite; Step (2): Heat 2250g of polyvinyl alcohol solution to 75℃, add sodium hydroxide solution to adjust pH=9.5, add 337g of 2,3-epoxypropyltrimethylammonium chloride, react for 5h, cool to room temperature, adjust pH to neutral, and obtain modified polyvinyl alcohol solution; Step (3): Mix 2250g of modified polyvinyl alcohol solution and 340g of 6-aminoquinoline evenly, react for 4h, introduce nitrogen gas, add 850g of isocyanate methacrylate and 17g of dibutyltin dilaurate, react at 70℃ for 7h, cool to room temperature, add deionized water to obtain solution A with a solid content of 20%. Step (4): Mix 2250g of solution A and 180g of pretreated fluorinated graphite evenly, introduce nitrogen gas, add 270g of 3,4-ethylenedioxythiophene, adjust the pH of the system to 2.5 with 1mol / L hydrochloric acid, add 10.8g of ammonium persulfate dropwise over 40min, react for 23h under ice-water bath conditions, and obtain modified fluorinated graphite after centrifugation, washing and drying.

[0040] Example 4: A method for preparing fluorinated graphite, comprising the following steps: Graphite was placed in a fluorination reactor, F2 was introduced, and the pressure in fluorination reactor 2 was controlled at 150 kPa to carry out the fluorination reaction (reaction temperature 500℃, reaction time 5 h) to obtain fluorinated graphite. When the pressure in the fluorination reactor exceeded 200 kPa, the pressure relief valve was opened, and the fluorinated gas source was cooled in a cooler, and then circulated back to the fluorination reactor by a gas circulation pump. The gas circulation pump controlled the gas flow rate at 1.0 m³ / h. 3 / h; A method for preparing a positive electrode sheet for a lithium fluoride carbon battery includes the following processes: Step S1: Mix 190g of fluorinated graphite, 20g of conductive agent, 20g of binder and N-methylpyrrolidone evenly to obtain a positive electrode slurry with a solid content of 70%; Step S2: Coat the positive electrode slurry onto the current collector, dry it, and then roll it to obtain the positive electrode sheet of the lithium fluoride carbon battery; Fluorinated graphite undergoes modification treatment, the specific process of which is as follows: Step (1): Fluorinated graphite is subjected to mixed plasma treatment (the process conditions for plasma treatment are: working atmosphere is C2H2 / Ar, C2H2:Ar=1:2, treatment time is 20min, treatment power is 250W, vacuum degree is 40Pa, and treatment temperature is 300℃) to obtain pretreated fluorinated graphite; Step (2): Heat 1900g of polyvinyl alcohol solution to 80℃, add sodium hydroxide solution to adjust pH=10, add 380g of 2,3-epoxypropyltrimethylammonium chloride, react for 6h, cool to room temperature, adjust pH to neutral, and obtain modified polyvinyl alcohol solution. Step (3): Mix 1900g of modified polyvinyl alcohol solution and 380g of 6-aminoquinoline evenly, react for 5h, introduce nitrogen gas, add 1140g of isocyanate methacrylate and 34.2g of dibutyltin dilaurate, react at 75℃ for 8h, cool to room temperature, add deionized water to obtain solution A with a solid content of 20%; Step (4): Mix 1900g of solution A and 190g of pretreated fluorinated graphite evenly, introduce nitrogen gas, add 380g of 3,4-ethylenedioxythiophene, adjust the pH of the system to 3 with 1mol / L hydrochloric acid, add 19g of ammonium persulfate dropwise over 50min, react for 24h under ice-water bath conditions, and obtain modified fluorinated graphite after centrifugation, washing and drying.

[0041] Comparative Example 1: A method for preparing fluorinated graphite, comprising the following processes: Compared to Example 1, the gas flow rate in Comparative Example 1 was 0.3 m³ / s. 3 / h, the other steps are the same as in Example 1.

[0042] Comparative Example 2: A method for preparing fluorinated graphite, comprising the following processes: Compared to Example 1, the gas flow rate in Comparative Example 2 was 1.5 m³ / s. 3 / h, the other steps are the same as in Example 1.

[0043] Comparative Example 3: A method for preparing a positive electrode sheet for a lithium fluoride carbon battery, comprising the following processes: Compared with Example 3, Comparative Example 3 does not include step (1), but the other steps are the same as in Example 3.

[0044] Comparative Example 4: A method for preparing a positive electrode sheet for a lithium fluoride carbon battery, comprising the following processes: Compared with Example 3, Comparative Example 4 replaced solution A with the same mass of polyvinyl alcohol solution, and the other steps were the same as in Example 3.

[0045] experiment: Experiment 1: Fluorinated graphite obtained from Examples 1-4 and Comparative Examples 1-2 was tested, and the results are shown in Table 1.

[0046] Table 1 Performance tests of fluorinated graphite in Examples 1-4 and Comparative Examples 1-2

[0047] Experiment 2: The positive electrode sheets of lithium fluoride carbon batteries obtained in Examples 1-4 and Comparative Examples 3-4 were cut into 12mm diameter discs and placed in an Ar-protected glove box (oxygen and water content less than 0.1ppm). They were assembled in the order of negative electrode shell, negative electrode sheet, separator, positive electrode sheet, gasket, spring sheet and positive electrode shell, and sealed with a battery sealing machine to obtain a button battery. During the assembly process, one drop of electrolyte was added to each side of the separator to ensure the wetting effect of the electrolyte. The battery shell model was CR2032, the negative electrode sheet was a lithium metal sheet, the separator was Celgard 2400 material, and the electrolyte was an organic solution of 0.8M LiPF6 dissolved in ethylene carbonate: diethyl carbonate (EC:DEC) at a ratio of 1:1. The charge and discharge performance of the batteries was tested using a LAND CT2001A battery tester (Wuhan Landian). The button batteries were tested at different rates (0.2C, 0.5C, 1C, 2C) with a voltage range of 2.0-3.65V. The 0.1C discharge capacity was used as the baseline of 100%. The test results are shown in Table 2.

[0048] Table 2 Performance Tests of Lithium-Coated Carbon Fluoride Battery Positive Electrodes in Examples 1-4 and Comparative Examples 3-4

[0049] Based on the data in the table above, the following conclusions can be clearly drawn: 1. Compared with Example 1, the rate performance of the products obtained in Examples 2-4 is improved, indicating that the present invention modifies fluorinated graphite and effectively enhances its electrochemical performance.

[0050] 2. Compared with Examples 2-4, the rate performance of the products obtained in Comparative Examples 3-4 decreased, indicating that the C2H2 / Ar mixed plasma modification of fluorinated graphite in this invention can effectively improve its electrochemical performance and rate capability; at the same time, compared with polyvinyl alcohol solution, solution A prepared in this invention has better reactivity and can achieve a better coating effect.

[0051] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process method article or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process method article or apparatus.

[0052] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.

Claims

1. A method for preparing fluorinated graphite, characterized in that: Includes the following steps: Graphite is placed in a fluorination reactor (2), and a fluorinated gas source (1) is introduced. The pressure in the fluorination reactor (2) is controlled at 100-150 kPa to carry out the fluorination reaction and obtain fluorinated graphite. When the pressure in the fluorination reactor (2) exceeds 200 kPa, the pressure relief valve (3) is opened, and the fluorinated gas source enters the cooler (4) for cooling, and then enters the gas circulation pump (5) for circulation back to the fluorination reactor (2). The gas circulation pump (5) controls the gas flow rate to be 0.5-1.0 m³ / s. 3 / h; The fluorinated graphite undergoes modification treatment, the specific process of which is as follows: Step (1): Fluorinated graphite is subjected to mixed plasma treatment to obtain pretreated fluorinated graphite; Step (2): Heat the polyvinyl alcohol solution to 70-80℃, add sodium hydroxide solution to adjust the pH to 9-10, add 2,3-epoxypropyltrimethylammonium chloride, react for 4-6 hours, cool to room temperature, adjust the pH to neutral, and obtain the modified polyvinyl alcohol solution. Step (3): Mix the modified polyvinyl alcohol solution and 6-aminoquinoline evenly, introduce nitrogen gas, add isocyanate methacrylate and dibutyltin dilaurate, react at 65-75℃ for 6-8h, cool to room temperature, add deionized water to obtain solution A; Step (4): Mix solution A and fluorinated graphite evenly, introduce nitrogen gas, add 3,4-ethylenedioxythiophene, adjust the pH of the system to 2-3 with hydrochloric acid, add ammonium persulfate dropwise over 30-50 minutes, react under ice-water bath conditions for 22-24 hours, and obtain modified fluorinated graphite after centrifugation, washing and drying.

2. The method for preparing fluorinated graphite according to claim 1, characterized in that: The fluorinated gas source (1) is one or more of F2, ClF, ClF3, and NF3.

3. The method for preparing fluorinated graphite according to claim 1, characterized in that: The reaction conditions of the fluorination reactor (2) are: reaction temperature 300-500℃, reaction time 5-30h.

4. The method for preparing fluorinated graphite according to claim 1, characterized in that: In step (1), the plasma treatment process conditions are as follows: working atmosphere is C2H2 / Ar, C2H2:Ar=1:(1-2), treatment time is 10-20min, treatment power is 200-250W, vacuum degree is 15-40Pa, and treatment temperature is 25-300℃.

5. A fluorinated graphite prepared according to any one of claims 1-4.

6. A method for preparing a positive electrode sheet for a lithium fluoride carbon battery, characterized in that: Includes the following steps: Step S1: Mix the fluorinated graphite, conductive agent, binder and solvent as described in claim 5 evenly to obtain the positive electrode slurry; Step S2: Coat the positive electrode slurry onto the current collector, dry it, and then roll it to obtain the positive electrode sheet of the lithium fluoride carbon battery.

7. The method for preparing a lithium fluoride carbon battery positive electrode sheet according to claim 6, characterized in that: The mass ratio of the fluorinated graphite, conductive agent and binder is (80-95):(2-10):(3-10).

8. A lithium fluoride carbon battery, characterized in that: The lithium fluoride battery contains a lithium fluoride battery positive electrode as described in claim 6.

Citation Information

Patent Citations

  • Industrial novel method for synthesizing graphite fluoride

    CN101486454A

  • Plasma modified carbon fluoride positive electrode material and preparation method and application thereof

    CN112723337A